- #1

adrian116

- 43

- 0

Since the question quite long and contains many formulas,

so i take a photo instead.

my question is that for part b

since [itex] Z= \sqrt{R^2+(X_L-X_C)^2} [/itex]

can i subst [itex] X_L = (W_0+\triangle{\omega})L [/itex]

and [itex] X_C = \frac{1}{(w_0+\triangle{\omega})L} [/itex]

into the [itex] Z= \sqrt{R^2+(X_L-X_C)^2} [/itex]

if it does, can u show me some of steps ?

I can derive the result from the problem in part b

By the way, what do the amplitude of current is half the resonance value?

is it [itex] I=\frac{\omega}{2} [/itex] ?

so i take a photo instead.

my question is that for part b

since [itex] Z= \sqrt{R^2+(X_L-X_C)^2} [/itex]

can i subst [itex] X_L = (W_0+\triangle{\omega})L [/itex]

and [itex] X_C = \frac{1}{(w_0+\triangle{\omega})L} [/itex]

into the [itex] Z= \sqrt{R^2+(X_L-X_C)^2} [/itex]

if it does, can u show me some of steps ?

I can derive the result from the problem in part b

By the way, what do the amplitude of current is half the resonance value?

is it [itex] I=\frac{\omega}{2} [/itex] ?

#### Attachments

Last edited: